The extended tanh method for solving some evolution equations - Dahmani, Zoubir; Mesmoudi, Mohammed Mostefa; Bebbouchi, Rachid (International Journal of Nonlinear Science, 2009)
In this paper we use the extended tanh method to formally derive traveling wave solutions for some evolution equations of the type u t − Du xx = ( B 0 + B 1 u ) u x + A 3 u 3 + A 2 u 2 + A 1 u + A 0 . The obtained solutions include, also, kink solutions. The extended tanh method presents a wide applicability for handling nonlinear evolution equations.
Keywords: Extended tanh method, Kink solutions, Nonlinear evolution equations, Traveling wave solutions.